Analysis on the Effect of the Uncertainty of Outside Power on the Equilibrium of Joint Energy and Reserve Market. Issue 4 (May 2019) - Zhu, Bingquan; Lin, Kaiying; Zhao, Nan; Li, Jihong; Xiao, Yanwei; Wang, Beibei
Abstract: As a major way to consume new energy, energy transmission across provinces and regions has increased rapidly in recent years. It is of great importance for the construction of the spot market to study the impact of different uncertainty of the outside power on the joint energy and reserve market. Firstly, this paper establishes a joint energy and reserve market equilibrium model that takes into account the uncertainty of the outside power which leads to additional reserve demand. Secondly, a game equilibrium algorithm is proposed to solve the market final equilibrium. The simulation results show that the uncertainty of the outside power will not only reduce market efficiency but also damage the interests of the outside new energy generator itself.